Evidence for a novel, neurohumoral antinociceptive mechanism mediated by peripheral capsaicin-sensitive nociceptors in conscious rats. (April 2017) - Pethő, Gábor; Bölcskei, Kata; Füredi, Réka; Botz, Bálint; Bagoly, Teréz; Pintér, Erika; Szolcsányi, János
Abstract: Stimulation of capsaicin-sensitive peripheral sensory nerve terminals induces remote anti-inflammatory effects throughout the body of anesthetized rats and guinea-pigs mediated by somatostatin. As somatostatin has also antinociceptive effects, the study aimed at investigating whether similar remote antinociceptive effects can be demonstrated in awake animals. In conscious rats, nociceptive nerve endings of the right hind paw decentralized by cutting the sciatic and saphenous nerves 18 h before were chemically stimulated, and drop of the noxious heat threshold (heat hyperalgesia) induced by prior (18 h before) plantar incision was measured on the contralateral, left hind paw using an increasing-temperature water bath. 18 h after nerve transection, mustard oil-evoked plasma extravasation was not significantly reduced in the right hind paw as tested by in vivo fluorescence imaging. Applying agonist of either transient receptor potential vanilloid 1 (TRPV1) or transient receptor potential ankyrin 1 (TRPA1) receptor (capsaicin or mustard oil, respectively) to the nerve-transected paw inhibited the plantar incision-induced drop of the noxious heat threshold on the contralateral paw. The onset of these remote antihyperalgesic effects was 10–20 min. A similar contralateral inhibitory effect of capsaicin or mustard oil treatment was observed on neuropathic mechanical hyperalgesia evoked by partial sciatic nerve injury 2 days before nerve transection and measured by a Randall–Selitto apparatus. The remote thermal antihyperalgesic effect was prevented by chronic (5 days) denervation or local capsaicin desensitization of the stimulated paw; reduced by intraperitoneally applied antagonist of somatostatin (cyclosomatostatin) or opioid receptors (naloxone). The response was mimicked by intraperitoneally applied somatostatin and associated with a 72 ± 27% increase in plasma somatostatin-like immunoreactivity that was absent after chronic (5 days) denervation. In conclusion, chemical activation of decentralized peripheral capsaicin-sensitive nociceptors evokes remote antihyperalgesic responses initiated outside the central nervous system and mediated by somatostatin and endogenous opioids. Graphical abstract: Highlights: Chemical stimulation of peripheral nociceptors evokes remote antihyperalgesic effect. The remote antihyperalgesic effect is induced without central circuits. Antihyperalgesia is mediated by somatostatin and opioid peptides.